Strategic GIS Planning and Management in Local Government - Holdstock, David A (CRC Press, 2016)
This "how-to" book on planning and managing GIS within local government describes and details the key components of a successful enterprise, sustainable and enduring GIS. It describes the strategic planning process an organization must undertake prior to GIS implementation. The heart of the book is the formula for success that offers a systematic methodology for examining and benchmarking a GIS initiative and the practical and repeatable strategy for success. There are many obstacles to successful GIS implementation, and unfortunately, the local government landscape is riddled with false starts, poorly planned implementations, and glorified mapping systems. This book documents the reason for failure and possible remedies to overcome the challenges to implementation. It discusses pathways to change, ways of improving organizational effectiveness and efficiency, and lays out the organizational approaches, management processes, and leadership actions that are required for GIS to become an indispensable part of an organization. This book is about aiming high, so you can consistently hit your mark by formulating goals and objectives that will tremendously influence the success of a GIS initiative. It details the factors crucial for building an enterprise GIS vision statement that includes governance, data and databases, procedures and workflow, GIS software, GIS training and education, and infrastructure, and how to develop performance measures related to the stated objectives of an organization. The book combines theory with real-world experience to offer guidance on the process of managing GIS implementation. Through key components, this book introduces a new way to think about GIS technology. Preface Acknowledgments Author Introduction Strategic Planning The Formula for Success Challenges, Barriers, and Pitfalls Developing a Vision, Goals, and Objectives Governance GIS Training, Education, and Knowledge Transfer Return on Investment How to Sell GIS to Local Government? Conclusions Strategic Planning A Proposed Outline for the Scope of Work Phase I: Needs Assessment Step 1: Online Questionnaire Step 2: Kick-Off Meeting and Technology Workshop Step 3: Departmental Interviews Step 4: Present the Findings of the GIS Needs Assessment Phase II: Conceptual Alternative System Design Step 5: Developing the CSD Phase III: Final Implementation Plan Step 6: Business Plan Step 7: Final Implementation Plan and Presentation (Plan of Action) The Formula for Success Different Perspectives on GIS A Layman’s Discussion of Campbell and Masser’s Book GIS and Organizations Technological Determinism : The IT Guru or Tech Geek Perspective Managerial Rationalism : The Local Government Management Perspective Social Interactionism : The Local Government Individual Perspective The Truth of the Matter The Formula for Success—A Checklist Category One: GIS Governance Category Two: GIS Digital Data and Databases Category Three: GIS Procedures, Workflow, and Integration Category Four: GIS Software Category Five: GIS Training, Education, and Knowledge Transfer Category Six: GIS Infrastructure The Formula for Success Challenges, Barriers, and Pitfalls A Pass/Fail Approach Five GIS Strategic Planning Components Component One: Strategic GIS Components Component Two: Tactical GIS Components Component Three: Technical GIS Components Component Four: Logistical GIS Components Component Five: Political GIS Components Challenges, Barriers, and Pitfalls Challenges to an Enterprise GIS Barriers to an Enterprise GIS Pitfalls to an Enterprise GIS The Challenges, Barriers, and Pitfalls of 100 Organizations The Challenges, Barriers, and Pitfalls during GIS Maturation The Role and Responsibilities of the GIS Coordinator Sequential Steps to Developing a Vision, Goals, and Objectives Step One: Understand the Existing GIS Situation Step Two: Conduct Blue Sky GIS Sessions with Stakeholders and Conduct a GIS SWOT Analysis Step Three: Build Consensus and Buy-In for an Enterprise GIS Solution from All Stakeholders Example 1: San Luis Obispo County, CA Example 2: City of Carlsbad, CA Example 3: Orange County, CA Example 4: City of Dayton, OH Example 5: Brant County, Ontario, Canada Example 6: Greenville Utilities Commission Example 7: City of Virginia Beach, VA Step Four: Align the GIS with the Vision of the Organizations Organization’s Overall Goal #1: Continually Improve Public Safety Organization’s Overall Goal #2: Sound and Stable Utilities Organization’s Overall Goal #3: Promote Economic Development Organization’s Overall Goal #4: A Great Downtown Organization’s Overall Goal #5: Increased Civic Engagement Organization’s Overall Goal #6: Promote Fiscal Soundness Step Five: Create a GIS Vision Statement, Goals, and Objectives GIS Vision Statement GIS Goals GIS Objectives Step Six: Develop Performance Measures, Outcomes, and Metrics Governance But What Exactly Is GIS Governance? New Management Challenges Introduced by GIS Implementation Government without GIS Misguided GIS Governance Why Is It So Challenging to Deploy an Optimum GIS Governance Model that Meets a Set of Basic Criteria? Three GIS Governance Models Governance Model #1: Centralized Governance Structure Governance Model #2: Decentralized Governance Model Governance Model #3: Hybrid Governance Model New Trending Governance Model: Regionalized Governance Model Adding Functional Teams to the Mix of Governance Models Departmental Accountability, Best Business Practices, Executive Champion, GIS Technical Committee, GIS Steering Committee, Subject Matter Experts, and GIS User Groups An Evaluation of the Different Governance Models Case Study Discussion